The effect of sintering duration on metal matrix composite reinforced with CNT fabricated by powder metallurgy: a review / Anis Safia Azrin and Saidatulakmar Shamsuddin - Azrin, Anis Safia; Shamsuddin, Saidatulakmar (Penerbit UiTM (UiTM Press), 2024)
Metallic alloys have broad applicability due to their characteristics, but there are still opportunities to improve on it or remove their constituent flaws that comes from their pure metallic form. Lightweight metals such as magnesium and aluminum have excellent strength-to-weight ratio, but they suffer from issues such as the tendency to ignite at high temperatures, porosity, and oxidation even when it is alloyed, which can be a safety risk when used in aircrafts or automobiles. Hence methods to overcome it include fabricating metal matrix composites (MMC) from metals such as aluminum, magnesium, titanium, and copper with carbon nanotubes (CNT) as a reinforcing material using powder metallurgy. Fabrication of such materials requires identification of important parameters to ensure the product has ideal characteristics. Thus, this study aims to identify and determine how the parameter of sintering duration in powder metallurgy and various factors of CNT, such as its concentration in the matrix, affects the mechanical properties of MMCs. This review is to encourage future breakthroughs and research in MMCs and powder metallurgy, as well as the usage of CNT in MMCs for any applicable fields that rely on such materials as the data obtained in this study can assist in the synthesis of MMCs.